2021
DOI: 10.1093/biolre/ioab158
|View full text |Cite
|
Sign up to set email alerts
|

Exposures during the prepuberty period and future offspring’s health: evidence from human cohort studies†

Abstract: Emerging evidence suggests that exposures in pre-puberty, particularly in fathers-to-be, may impact the phenotype of future offspring. Analyses of the RHINESSA cohort find that offspring of father’s exposed to tobacco smoking or overweight that started in pre-puberty demonstrate poorer respiratory health in terms of more asthma and lower lung function. A role of pre-puberty onset smoking for offspring fat mass is suggested in the RHINESSA and ALSPAC cohorts, and historic studies suggest that ancestral nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…A subsequent detailed study of antecedents associated with fat mass at age 24 showed that a similar association remained with paternal onset of smoking < 11 years, which increased in size on adjustment for confounders 9 . There is support for these findings since the association of fathers’ prepubertal onset of smoking with fat mass in sons but not daughters was also found in the RHINESSA study 4 .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…A subsequent detailed study of antecedents associated with fat mass at age 24 showed that a similar association remained with paternal onset of smoking < 11 years, which increased in size on adjustment for confounders 9 . There is support for these findings since the association of fathers’ prepubertal onset of smoking with fat mass in sons but not daughters was also found in the RHINESSA study 4 .…”
Section: Introductionmentioning
confidence: 63%
“…The most recent population studies to investigate this have largely focussed on asthma as the outcome of interest. The authors have shown paternal exposures to smoking of cigarettes prepuberty to be associated with increased risk of asthma and reduced lung function as well as of increased fat mass in the offspring 4 .…”
Section: Introductionmentioning
confidence: 99%
“…To have a beneficial or adverse effect on human health, the environmental exposure in question must interact with the biological system at some level, i.e., it must be bioavailable for the target cell at the right time and be able to interact with biomolecules. An optimal assessment of the exposome during the preconception period would require access to the germ cells of the parent and, perhaps, of previous generations, as well as (surrogate) target tissues in the next generation [ 6 ]. The human germ cells and the microenvironments of these in the ovaries/testes are unavailable for research in the prepuberty window, in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Validation analyses from the same cohorts on information reported across two generations showed that recall bias is likely to have a limited impact on these results [ 33 , 34 ]. Three-generation causal associations of the smoking of grandmothers and grandfathers on the lung function of offspring within the paternal line were assessed in the ECRHS and RHINESSA cohorts [ 30 ], using a causal modeling approach [ 6 , 32 , 35 ]. The father’s smoking in prepuberty appeared to cause lower lung function in offspring, with a negative direct effect on the offspring’s forced expiratory volume in one second (FEV 1 ) and forced vital capacity (FVC).…”
Section: Preconception Exposures and Respiratory Health: Evidence From Multigeneration Studies On Humansmentioning
confidence: 99%
See 1 more Smart Citation